Systematics and species recognition in Oneilliella Wilson (Thripidae: Panchaetothripinae) - Lima, Élison Fabrício B.; Vieira, Daniel E.; O’donnell, Cheryle A.; Mound, Laurence A. (Zootaxa, 2023)
Oneilliella is a poorly sampled Panchaetothripinae genus with two described species based on very few specimens. Here we provide further information about the genus and describe three species: O. chicoi sp. n. and O. wanessae sp. n. from Brazil, and O. tica sp. n. from Costa Rica. We discuss the relationships between Oneilliella and other members of Panchaetothripinae based on morphology. The Indian species Oneilliella shivii Singha et al. requires further study as it is probably not congeneric with the Neotropical lineage recognized here. An illustrated key to the five Oneilliella species is provided.